The Contribution of Women on Corporate Boards: Board’s Effectiveness – Focus on ICT - Ivona Miholić; Marina Klačmer Čalopa; Ivana Đunđek Kokotec (Journal of Information and Organizational Sciences, 2022)
The composition of supervisory and board of directors in companies is extremely important for the successful operation of companies. Nowadays, women in the workplace, and especially in management positions, encounter a form of discrimination that has its own professional name - the phenomenon of "glass ceiling". Therefore, it is very important to analyze the representation of women and men on the company’s supervisory board and board of directors. This paper will explain women's leadership style, differences between men's and women's leadership style, and the problems that women in employment, and especially in promotion. The aim off this paper is to determine whether the “glass ceiling” phenomenon is prominent in Croatian companies and to what extent. In addition, women’s representation in senior positions will be related to business performance criteria.